An Analysis of Code Mixing and Code Switching on Cinta Laura’s Video “Kuliah Keluar Negeri Itu Perlu Gak Sih?” - Fresya, Octaviola; Adiantika, Hanif Nurcholish; Susilawati, Susilawati (Ma'soem University, 2024)
When two or more languages are switched during a monologue or dialog, sociolinguistics who research language used to refer to it as